The impact of wireless technology towards users’ acceptance among rural area residents at Kampung Sawah Baru, Segamat, Johor / Nurhana Diba Yusof...[et al] - Diba Yusof, Nurhana (Faculty of Business and Management, 2013)
Budget 2010 stressed the importance of innovation included in tenn of urban rural innovation to encourage people to use leT and Internet facilities and help reduce the digital divide that exists between the urban and rural areas. The wireless network was implemented a few month of 2011 year with the intention of offering the rural area residents easy connectivity. Nevertheless, it was found that users having problems in connecting to the Wireless networks mainly at the users living area. Therefore this study was conducted to defme the most influence element of wireless technology perceived usefulness and perceived ease of use towards users' acceptance among rural area residence in Kampung Sawah Baru, Segamat lohor. The survey technique was used in conducting this study by distributed questionnaires to 88 samples. Based on the survey conducted its shows there have significant relationship between perceived usefulness and perceived ease of use towards user acceptance in Kampung Sawah Baru, Segamat Johor.